The Rise of Coccidioides: Forces Against the Dust Devil Unleashed - Van Dyke, Marley C. Caballero; Thompson, George R.; Galgiani, John N.; Barker, Bridget M. (Frontiers in Immunology, 2019)
Coccidioidomycosis (Valley fever) is a fungal disease caused by the inhalation of Coccidioides posadasii or C. immitis. This neglected disease occurs in the desert areas of the western United States, most notably in California and Arizona, where infections continue to rise. Clinically, coccidioidomycosis ranges from asymptomatic to severe pulmonary disease and can disseminate to the brain, skin, bones, and elsewhere. New estimates suggest as many as 350,000 new cases of coccidioidomycosis occur in the United States each year. Thus, there is an urgent need for the development of a vaccine and new therapeutic drugs against Coccidioides infection. In this review, we discuss the battle against Coccidioides including the development of potential vaccines, the quest for new therapeutic drugs, and our current understanding of the protective host immune response to Coccidioides infection.